Trade and Investment Performance Under Floating Exchange Rates : The U.S. Experience. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Contrary to the arguments of several scholars, we have failed to find either a conclusive theoretical case or clear empirical evidence of an effect, harmful or otherwise, of exchange rate variability (as measured by either short-term volatility or long-run misalignment) on overall levels of international trade. In this paper, after reviewing the theories and evidence on this issue, we go on to consider the impact of exchange rate variability on direct foreign investment. We summarize and amplify upon the scant theoretical literature of this issue, and proceed to test U.S. data for the presence of such an impact. We find none.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet